Literature, gender and politics during the English Civil War - Purkiss, Diane, 1961- (Cambridge University Press, 2005)
Diane Purkiss illuminates the role of gender in the English Civil War by analysing representations of masculinity in the writings of Milton, Marvell, Waller and Herrick. This study will appeal to scholars of seventeenth-century literature as well as those working in intellectual history and the history of gender.